Kontribusi Magang Terhadap Pengembangan Ketrampilan Hukum (Studi Kasus Di Kantor Pengacara Tri Wira Justitia) - Chindy Afrilia; Martono Anggusti; Yosua Tahyudi R. Panjaitan (Mahesa Research Center, 2024)
Internship programs have an important role in developing law students' practical skills, especially in preparing them to enter the professional world. This research aims to explore the contribution of internships at Tri Wira Justitia Law Firm to the development of students' legal skills. The method used is a qualitative case study with interviews, observation, and document analysis as data collection techniques. The results showed that the internship program provided significant improvements in case analysis skills, legal document drafting, professional communication, as well as understanding of legal ethics. In addition, the internship also strengthened time management and conflict handling skills. In conclusion, the internship at Tri Wira Justitia Law Firm made a great contribution in preparing students for the world of legal work.